Galectin-3: Roles in Neurodevelopment, Neuroinflammation, and Behavior - Ivan Srejovic; Dragica Selakovic; Nemanja Jovicic; Vladimir Jakovljević; Miodrag L. Lukic; Gvozden Rosic (Biomolecules, 2020)
There is a plethora of evidence to suggest that Galectin-3 plays an important role in normal functions of mammalian cells, as well as in different pathogenic conditions. This review highlights recent data published by researchers, including our own team, on roles of Galectin-3 in the nervous system. Here, we discuss the roles of Galectin-3 in brain development, its roles in glial cells, as well as the interactions of glial cells with other neural and invading cells in pathological conditions. Galectin-3 plays an important role in the pathogenesis of neuroinflammatory and neurodegenerative disorders, such as multiple sclerosis, Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease. On the other hand, there is also evidence of the protective role of Galectin-3 due to its anti-apoptotic effect in target cells. Interestingly, genetic deletion of Galectin-3 affects behavioral patterns in maturing and adult mice. The results reviewed in this paper and recent development of highly specific inhibitors suggests that Galectin-3 may be an important therapeutic target in pathological conditions including the disorders of the central nervous system.